Lippincott's primary care rheumatology - Boulware, Dennis W.; Heudebert, Gustavo R. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2012)
"This volume of Lippincott's Primary Care Series will help family practitioners, internists, nurse practitioners, and physician assistants understand, diagnose, and treat the most common rheumatologic problems seen in the primary care setting. Emphasis on day-to-day practical outpatient office practice distinguishes this from the many existing rheumatology textbooks and it contains numerous images to aid in diagnosis and treatment. Whenever possible, chapters follow a consistent format with headings of Clinical Presentation, Examination, Studies, Treatment, Clinical Course, and Conclusions and box elements such as Introductory Case, Clinical Points/Highlights, Patient Assessment, Not to Be Missed, and When to Refer. Key points are provided for those topics that don't fit this format"--Provided by publisher.
Machine generated contents note: Section 1: INTRODUCTION TO THE RHEUMATIC DISEASES 1. Evaluation of Patients with Rheumatic DiseasesCarlos A. Estrada and Gustavo R. Heudebert Section 2: SPORT-RELATED, OCCUPATIONAL AND OTHER REGIONAL PAIN SYNDROMES 2. Neck PainJerome Van Ruiswyk 3. Lower Back Pain and Lumbar StenosisLisa L. Willett 4. Shoulder Pain Dennis W. Boulware 5. Painful FeetDennis W. Boulware and Gustavo R. Heudebert 6. Mechanical Disorders of the KneeDennis W. Boulware 7. Hip PainCarol Croft 8. Sports-related Conditions and InjuriesLisa L. Willett Section 3: SPECIFIC RHEUMATIC DISEASES: DIAGNOSIS AND TREATMENT 9. Rheumatoid Arthritis including Sjogren's SyndromeZachary M. Pruhs, James R. O'Dell, and Ted R Mikuls 10. The Seronegative Spondyloarthropathies Dennis W. Boulware 11. Systemic Lupus Erythematosus Michelle A. Petri 12. Raynaud's Phenomenon and Systemic Sclerosis Laura B. Hughes and Barri Fessler 13. Inflammatory Myopathies: Polymyositis, Dermatomyositis, and Related Conditions Irene Z. Whitt and Frederick W. Miller 14. Vasculitis Bao Quynh N. Huynh and S. Louis Bridges, Jr. 15. Giant Cell Arteritis and Polymyalgia Rheumatica Angelo Gaffo 16. Overlap Syndromes and Unclassified or Undifferentiated Connective Tissue Disease Iris Navarro and Graciela S. Alarcon 17. Fibromyalgia Graciela S. Alarcon 18. Pregnancy and Rheumatic Diseases Michael Lockshin Section 4: OSTEOARTHRITIS AND METABOLIC BONE AND JOINT DISEASE 19. OsteoarthritisSeth M. Berney 20. Gout and Crystal-induced Arthropathies Angelo Gaffo 21. Osteopenic Bone Disease and Osteonecrosis Kenneth G. Saag, Gregory A. Clines, and Sarah L. Morgan 22. Arthropathies Associated with Systemic Diseases Leann Maska and Amy C. Cannella Section 5: INFECTIOUS ARTHRITIS 23. Bacterial ArthritisArthur Kavanaugh and Maika Onishi 24. Lyme Disease William F. Iobst and Kristin Ingraham 25. Viral Arthritis Martin Rodriguez and Katherine Holman Section 6: SPECIAL DIAGNOSTIC AND THERAPEUTIC CONDITIONS 26. Use of the Laboratory in Diagnosing Rheumatic Disorders Gustavo R. Heudebert and Terry Shaneyfelt 27. Techniques of Arthrocentesis Dennis W. Boulware 28. Monitoring of Patients on Antirheumatic Therapy W. Winn Chatham.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Rheumatology; Primary care (Medicine); Electronic books